A knowledge, attitudes, and practices study on ticks and tick-borne diseases in cattle among farmers in a selected area of eastern Bhutan - Namgyal, Jamyang; Tenzin, Tenzin; Checkley, Sylvia; Lysyk, Tim J.; Rinchen, Sangay; Gurung, Ratna B.; Dorjee, Sithar; Couloigner, Isabelle; Cork, Susan C. (PloS one, 2021)
Livestock farming plays an important role in supporting the livelihood of resource-poor subsistence farmers in Bhutan. However, ticks and tick-borne diseases (TBDs) are one of the major constraints to livestock farming due to their negative effect on health and production. To date, no study has been conducted in Bhutan to assess farmers’ knowledge, attitude, and practices (KAP) about ticks and TBDs in cattle, although such information is essential in ensuring the development and adoption of effective prevention and control measures. Therefore, a KAP survey was conducted among 246 cattle owners in the Samkhar sub-district of eastern Bhutan in June 2019, using a structured questionnaire. Based on our scoring criteria, 52% [95%CI: 45.5–58.4] had adequate knowledge about ticks as potential vectors of diseases. Logistic regression analysis showed that the individuals who practiced a stall-feeding system of cattle rearing were 2.8 times [OR = 2.8 (95%CI: 1.66–4.78)] more likely to have adequate knowledge than others. Sixty-eight percent [95%CI: 62.5–74.4] had a favorable attitude toward tick prevention and control programs. Men were 1.95 times [OR = 1.95 (95%CI: 1.09–3.55)] more likely to have a favorable attitude than women, and the individuals who practiced a stall-feeding system were 2.59 times [OR = 2.59 95%CI: 1.45–4.78)] more likely to have a favorable attitude than others, after adjusting for the effect of other variables in the model. Overall, only 38% [95%CI 32.5–45] of the respondents reported tick infestation as one of the most important animal health problems, but 100% reported using acaricides to control ticks in cattle. Despite a high level of acaricide usage, the level of knowledge was low among the farmers interviewed. Findings from this study underline the importance of considering identified knowledge gaps and initiating education efforts to improve the adoption of effective tick prevention and control measures among farmers.